2013
DOI: 10.1097/mat.0b013e3182816cd9
|View full text |Cite
|
Sign up to set email alerts
|

Total Artificial Heart Support with Two Continuous-Flow Ventricular Assist Devices in a Patient with an Infiltrating Cardiac Sarcoma

Abstract: Primary cardiac sarcoma is normally fatal, but cardiac replacement may provide some hope for long-term survival. A 38 year-old man with cardiac sarcoma, involving the interventricular septum and posterior wall with intermittent mitral obstruction, underwent implantation of two HeartMate II ventricular assist devices for total artificial heart support. After cardiectomy, the HeartMate sewing rings were sewn to the right neoatrium and the left atrial remnants. After the outflow grafts were sewn end to end to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Our research yielded 10 studies, the first published in 2002 by Sezai et al and the last in 2013 by Pirk et al Their characteristics are outlined in Table . They are all case reports and descriptions of surgical techniques, most reporting on one case only, except Latif et al who presented a series of 22 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research yielded 10 studies, the first published in 2002 by Sezai et al and the last in 2013 by Pirk et al Their characteristics are outlined in Table . They are all case reports and descriptions of surgical techniques, most reporting on one case only, except Latif et al who presented a series of 22 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Cardiomyopathy was also frequently observed. There is one case of cardiac amyloidosis reported by Frazier and Cohn, one of an intra‐cardiac tumor, and cases were the patient's heart had anatomic defects which where irreparable. Ubilla et al reported a case where the patient had multiple previous surgeries for aortic valve disease and was admitted for heart transplant, but technical considerations and the anticipation of a difficult dissection led the team to choose a two‐step procedure, removing the ventricle and implanting two VADs first before proceeding with the transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In patients with an early diagnosis and no metastases, several reports have described improved survival rates and increased disease-free intervals consequent to aggressive surgical and multimodal treatment with chemotherapy and RT. [8][9][10] These patients were alive and symptom-free at their follow-up evaluations 9 months or more after therapy.…”
Section: Fig 2 Photomicrographs Of Angiosarcoma In the Pericardium Smentioning
confidence: 99%
“…10 The risk of a patient's developing post-RT sarcoma can be reduced by careful selection of cancer patients in accordance with established guidelines on radiosensitive tumors and by choosing targeted therapy, such as intensity-modulated protonbeam RT over conventional RT. Proton-beam therapy, however, is not yet widely available and not yet proven.…”
Section: Fig 2 Photomicrographs Of Angiosarcoma In the Pericardium Smentioning
confidence: 99%